The Effectiveness of The Smart Indonesia Program at The Education Level of Junior High School in Plered District, Purwakarta Regency (Case Study at Junior High School 2 Plered) - Rismawati Rismawati; Lukmanul Hakim; Rudyk Nababan (PT ARRUS Intelektual Indonesia, 2023)
In a distribution or disbursement of aid funds for the Smart Indonesia Program, it is necessary to monitor and evaluate the implementationSmart Indonesia Program or disbursement of financial aidSmart Indonesia Program in JHS 2 Plered, so that you can find out what are the deficiencies and obstacles in implementing the program. that have been determined so that they can be corrected so that they can provide better service and supervision for students and parents of receiving studentsSmart Indonesia Program. The research method that we use is a qualitative research method with a type of research that is a case study. Researchers use the theory according to Duncan, namely (i) achieving goals, (ii) integration, and (iii) adaptation. Implementation research resultsSmart Indonesia Program at the JHS 2 Education Level, Plered has been running but not optimal, because it is still not certain who will receive it Smart Indonesia Program right on target because it takes time for monitoring or surveys to come to their homes, as well as the lack of supervision from the Dinas Pendidikan Purwakarta Office regarding the use or disbursement of financial aid Smart Indonesia Program.